Differential force scaling of fine-graded power grip force in the sensorimotor network - Keisker, Birgit; Hepp-Reymond, Marie-Claude; Blickenstorfer, Armin; Meyer, Martin; Kollias, Spyros S. (Human brain mapping, 2009)
Force scaling in the sensorimotor network during generation and control of static or dynamic grip force has been the subject of many investigations in monkeys and human subjects. In human, the relationship between BOLD signal in cortical and subcortical regions and force still remains controversial. With respect to grip force, the modulation of the BOLD signal has been mostly studied for forces often reaching high levels while little attention has been given to the low range for which electrophysiological neuronal correlates have been demonstrated. We thus conducted a whole‐brain fMRI study on the control of fine‐graded force in the low range, using a power grip and three force conditions in a block design. Participants generated on a dynamometer visually guided repetitive force pulses (ca. 0.5 Hz), reaching target forces of 10%, 20%, and 30% of maximum voluntary contraction. Regions of interest analysis disclosed activation in the entire cortical and subcortical sensorimotor network and significant force‐related modulation in several regions, including primary motor (M1) and somatosensory cortex, ventral premotor and inferior parietal areas, and cerebellum. The BOLD signal, however, increased monotonically with force only in contralateral M1 and ipsilateral anterior cerebellum. The remaining regions were activated with force in various nonlinear manners, suggesting that other factors such as visual input, attention, and muscle recruitment also modulate the BOLD signal in this visuomotor task. These findings demonstrate that various regions of the sensorimotor network participate differentially in the production and control of fine‐graded grip forces. Hum Brain Mapp 2009. © 2009 Wiley‐Liss, Inc.